HARMONISASI INTRA UMAT BERAGAMA DI KABUPATEN BIREUEN PASCA KONFLIK ANTARA MUHAMMADIYAH DAN NAHDATUL ULAMA - Amnar, Zuriah; Syah Iskandar (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
The conflict between Nahdatul Ulama (NU) and Muhammadiyah (MU) in Indonesia is basically not the first time this has occurred, including Aceh. As it is known that in Aceh the majority of Muslims are NU-oriented. The role of Ulama Dayah also influenced the turmoil between NU and MU in Aceh. Muhammdiyah's position as a Muslim minority and the understanding of the people who regard them as part of Wahhabism in Aceh became the strongest factors causing the conflict between the two camps. In Bireun Regency, precisely in Samalanga sub-district, the conflict between NU and MU has caused turmoil that resulted in the rejection of the mosque construction in 2016 to 2019. The purpose of this study is to examine how the intra-religious harmonization between NU and MU after the conflict. And how are the efforts made by the local government in mediating in solving the conflict between NU and MU. This research is a descriptive qualitative research with the type of field research (Field Research). The data collection technique was carried out using the documentation method on several sources related to the conflict between NU and MU in several print and online media. Then the researchers also made observations to the post-conflict community and finally conducted interviews with 1 resident and security forces in the Samalanga sub-district, Sangso village. Data analysis technique is done by reducing, presenting and concluding. The results showed that after the conflict related to the termination of the construction of the MU mosque in Samalanga District, Sangso Village, it had an impact on the disharmony of intra-religious people.